1975
DOI: 10.1590/s0074-02761975000200004
|View full text |Cite
|
Sign up to set email alerts
|

Alguns acantocéfalos de peixes do Oceano Atlântico, Costa Continental Portuguesa e Costa do Norte da África

Abstract: Foram estudadas quatro espécies de acantocéfalos encontrados na autópsia de 81 peixes capturados no Oceano Atlântico, na Costa Continental Portuguesa e na Costa Norte da África. Encontramos 16 peixes parasitados por acantocéfalos. As espécies de peixes necropsiados e os helmintos encontrados foram os seguintes: 11 meros (Epinephellus gigas) sendo 1 parasitado por fêmeas da família Rhadinorhynchidade; 5 sardas (Scomber scombrus) sendo duas parasitadas por Rhadinorhynchus tenuicornis; 62 pescadas (Merluccius mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The results of our morphological and phylogenetic study, along with the available epidemiological information on R. pristis infection in Scombridae and Xiphidae fishes from the nearby Portugal coast, the Madeira Islands and the North Atlantic, suggest that the cystacanths herein described probably belong to this species (Rodrigues et al 1975, Vassiliades 1982, Hogans et al 1983, Rego 1987, Costa et al 2004. However, we strongly recommend that a thorough review of the species, as well as the family Rhadinorhynchidae, should be carried out.…”
Section: Descriptionmentioning
confidence: 52%
See 1 more Smart Citation
“…The results of our morphological and phylogenetic study, along with the available epidemiological information on R. pristis infection in Scombridae and Xiphidae fishes from the nearby Portugal coast, the Madeira Islands and the North Atlantic, suggest that the cystacanths herein described probably belong to this species (Rodrigues et al 1975, Vassiliades 1982, Hogans et al 1983, Rego 1987, Costa et al 2004. However, we strongly recommend that a thorough review of the species, as well as the family Rhadinorhynchidae, should be carried out.…”
Section: Descriptionmentioning
confidence: 52%
“…(Rudolphi, 1802) in euphausiids from the NE Atlantic are available. With the exception of Rodrigues et al (1975) and Rego et al (1985), Rhadinorhynchus has not been reported in this area. In addition, these authors found adults of this genus infecting scombrid fishes.…”
Section: Introductionmentioning
confidence: 94%
“…According to Gibson and Bray (1986), H. appendiculatus appears to be restricted to A. alosa and A. fallax (especially in the latter) in Mediterranean and European Atlantic waters as far north as southern Norway (Moravec 2004). In addition, it was previously reported in A. fallax of the Atlantic coast of Africa and the Portuguese Coast (Rodrigues et al 1972cited in Aprahamian et al 2002.…”
Section: Hemiurus Appendiculatus (Rudolphi 1802)mentioning
confidence: 69%